Kecemasan (Anxiety Disorder) - Marianti, Lena; Aisyah, Nur; Kariza, Ajil; Fadillah, Nur; Mahbub, Muhammad Makki; Mustabsiro, M. (Jurnal Pendidikan Tambusai, 2026)
Anxiety disorders have surged post-COVID-19 in urban Indonesia, with daily stress, low social support, and negative thought patterns exacerbating symptoms among young adults, impairing daily functioning and academic performance. This study aimed to empirically analyze anxiety characteristics and Cognitive Behavioral Theory (CBT) application as contextual intervention using Beck Anxiety Inventory (BAI). Employing a quantitative descriptive approach, purposive sampling recruited 150 young adults (18-35 years) in urban areas; data were analyzed via SPSS descriptive statistics and Spearman correlations. Results revealed stress contributing 42% to anxiety variance, low support elevating risk 2.5-fold, and negative thinking 28% via rumination (r = -0.559, p < 0.05). Conclusions emphasize CBT's 60% symptom reduction efficacy, advocating multidisciplinary policy integration for prevention.